Measuring Langkawi sustainability as travel destination: validation through confirmatory factor analysis - Ismail, An Nur Nabila; Abdul Aziz, Yuhanis; Bali Mahomed, Anuar Shah; Kamal Basha, Norazlyn (Science & Engineering Research Support Society, 2020)
The environment and natural resources are is a reason that can attract tourist to visit. The main highlight of one particular tourism destination depends on the attractiveness and the beauty of its nature. Based on past literatures, limited study that focuses on the sustainability of the environment thus, this paper aims to validate several constructs that will be used to measure the sustainability of destinations. As Langkawi is one of the top destinations in Malaysia and recognized as a Global Geopark by United Nations Educational Scientific and Cultural Organization (UNESCO), it is a need to conduct a further research especially in term of sustainability. A total of 318 local and international tourists participated in this study and the data was collected by using self-administrated questionnaires. To confirm the construct, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) was adopted.The finding indicates that there are 15 constructs that can represent the destination sustainability. The study’s practical implication and limitation are discussed.